Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1038/s41598-017-09869-9
|View full text |Cite
|
Sign up to set email alerts
|

Linoleic acid metabolite leads to steroid resistant asthma features partially through NF-κB

Abstract: Studies have highlighted the role of nutritional and metabolic modulators in asthma pathobiology. Steroid resistance is an important clinical problem in asthma but lacks good experimental models. Linoleic acid, a polyunsaturated fatty acid, has been linked to asthma and glucocorticoid sensitivity. Its 12/15–lipoxygenase metabolite, 13-S-hydroxyoctadecadienoic acid (HODE) induces mitochondrial dysfunction, with severe airway obstruction and neutrophilic airway inflammation. Here we show that HODE administration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 48 publications
2
41
0
Order By: Relevance
“…Table 3). Prior studies from our laboratory have demonstrated elevated p-NF-kB in HODE induced steroid resistance in mice (11).…”
Section: Resultsmentioning
confidence: 81%
See 3 more Smart Citations
“…Table 3). Prior studies from our laboratory have demonstrated elevated p-NF-kB in HODE induced steroid resistance in mice (11).…”
Section: Resultsmentioning
confidence: 81%
“…It was also observed that HODE treated human bronchial epithelia had reduced GRα transcript levels and activity. Further, NF-κB was observed to be partially involved in HODE mediated steroid resistance in mice (11). In the present study, we investigated the plausible mechanism of steroid resistance using HODE treatment in a mice model of asthma.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…For example, the activation state of the transcription factor, nuclear factor kappa-B (NF-κB) is linked to adiponectin [43] and resistin [44], among others [45]. Further to this, NF-κB has been implicated in a number of conditions including cognitive decline, asthma [46], a number of cancers and chemotherapy response. As such, manipulating adipose-secreted factors offers opportunity to develop new treatment strategies [47]; yet the therapeutic potential of these factors has not yet come to fruition and the complexity of adipose tissue is still increasing.…”
Section: Adipokinesmentioning
confidence: 99%